1995
DOI: 10.1111/j.1399-6576.1995.tb04075.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypotensive treatment with α2‐agonist and β1‐antagonist on cerebral haemodynamics in severely head injured patients

Abstract: Therapy of post-traumatic brain oedema often includes preservation of high arterial blood pressure to avoid secondary ischaemic injuries to the brain. This practice can be questioned since high arterial blood pressure may aggravate brain oedema through raised hydrostatic capillary pressure, causing fluid filtration across the damaged blood-brain barrier. This latter view is in agreement with our clinical experience and therefore hypotensive therapy with an alpha 2-adrenergic agonist (clonidine) and a beta 1-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…43 Fale et al 44 further demonstrated in dogs, that dexmedetomidine limits the vasodilatory effect of raised PaCO 2 . No human studies have been performed to examine cerebral protection or ischaemia, however in rabbits and rats, dexmedetomidine conveys dose related cerebral protection from ischaemia, 45,46 and in dogs there was no evidence of cerebral ischaemia despite reductions of cerebral blood flow.…”
Section: Intracranial Surgerymentioning
confidence: 96%
See 1 more Smart Citation
“…43 Fale et al 44 further demonstrated in dogs, that dexmedetomidine limits the vasodilatory effect of raised PaCO 2 . No human studies have been performed to examine cerebral protection or ischaemia, however in rabbits and rats, dexmedetomidine conveys dose related cerebral protection from ischaemia, 45,46 and in dogs there was no evidence of cerebral ischaemia despite reductions of cerebral blood flow.…”
Section: Intracranial Surgerymentioning
confidence: 96%
“…a 2 -agonists have been implicated in the uncoupling of cerebral blood flow and cerebral metabolic requirement for oxygen, however other studies have shown that a 2 -agonists have no effect on cerebral metabolic requirement for oxygen. 41,43 Therefore, the clinical relevance of these findings is still unclear when reasonable blood pressure is maintained. Our application of this information has led to the safe and successful use of these agents for intracranial surgery over the last decade, with the caveats of particular care to maintain an adequate MAP with preoperative volume replacement and avoidance in patients with suspected acute raised ICP.…”
Section: Intracranial Surgerymentioning
confidence: 96%
“…The Lund concept includes reduction in systemic arterial pressure to decrease capillary hydrostatic pressure [11]. It has been well documented that hypotensive episodes can be deleterious in severe TBI [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…0.8 g/kg per 24 h) was used. Decreased hydrostatic capillary pressure in combination with preservation of normal colloid osmotic pressure induces transcapillary fluid absorption [10,11].…”
Section: Normotensionmentioning
confidence: 99%
See 1 more Smart Citation